Table of Content - - (Journal of engineering sciences and information technology, 2025)
Table of Content: • Sustainable Tourism Planning in The Kingdom of Saudi Arabia Eng. Ashraf Fawzy Hassan • Improving the Mechanical Properties of Hypereutectic Al–14%Si Alloy by Adding Alumina Particles of Different Sizes Using the Taguchi Method Eng. Farah. Ammar Ibrahim ,Prof. Zeyad D. Kadhim ,Prof. Mohammed Abdulraoof Abdulrazzaq • A Comparative Study of Safer Electrical Systems in Developing Countries-Quantitative Approach in Egypt and Iraq Dr. Hassan Kassem, Dr. Tariq Yousef Bishtawi • Modeling and Simulation of Induction Motor-Submersible Pump System with V/f Algorithm under Stator Short Circuit (SSC) Fault Dr. Ahmed Mohammad Khier Alkaoud • Edge AI for Real-Time Vision: Challenges, Limitations, and Future Research Directions Eng. Zamo Rzgar Ahmed